2021
DOI: 10.7150/thno.60902
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-derived EGFL6 couples angiogenesis to osteogenesis during bone repair

Abstract: Rationale: Angiogenesis and osteogenesis are highly coupled processes which are indispensable to bone repair. However, the underlying mechanism(s) remain elusive. To bridge the gap in understanding the coupling process is crucial to develop corresponding solutions to abnormal bone healing. Epidermal growth factor-like protein 6 (EGFL6) is an angiogenic factor specifically and distinctively up-regulated during osteoblast differentiation. In contrast with most currently known osteoblast-derived coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…47 The TGF-b, MAPK, and PI3K-Akt signaling pathways have been shown to regulate osteogenesis and bone metabolism. [48][49][50] Moreover, the Wnt and BMP signaling pathways are critical for the osteogenic differentiation of BMSCs. [44][45][46] Studies have also shown that suppressing the NF-kappa B signaling pathway can improve the osteogenic differentiation of stem cells.…”
Section: Results and Analysis Of Mrna Sequencingmentioning
confidence: 99%
“…47 The TGF-b, MAPK, and PI3K-Akt signaling pathways have been shown to regulate osteogenesis and bone metabolism. [48][49][50] Moreover, the Wnt and BMP signaling pathways are critical for the osteogenic differentiation of BMSCs. [44][45][46] Studies have also shown that suppressing the NF-kappa B signaling pathway can improve the osteogenic differentiation of stem cells.…”
Section: Results and Analysis Of Mrna Sequencingmentioning
confidence: 99%
“…Reproduced with permission. [ 242 ] Copyright 2021, PubMed Central. C) The addition of exogenous drug dexamethasone in bone regeneration.…”
Section: The Transformation From Man‐made Structure To Biological Str...mentioning
confidence: 99%
“…[241] Chen et al studied the function of epidermal growth factor-like protein 6 (EGFL6) in the osteogenic capacity of BMSCs and MC3T3-E1 cells, and the results indicated that EGFL6 enhanced osteogenic capacity and directed angiogenesis during bone repair. [242] Novais et al investigated the effect of FGF-2 in collagen hydrogels on the bone formation in the context of craniofacial bone repair and found that FGF-2 allowed a rapid compact extracellular matrix for favor bone formation. [247] Adv.…”
Section: Bone Defect Repairmentioning
confidence: 99%
“…EDITED BY multiple signals trigger BMSCs in bone marrow or surrounding tissues to migrate to the injured regions and play a paracrine role (Chen et al, 2021;Du et al, 2021;Sheng et al, 2022). In addition, BMSCs also have a hand in the healing stages of inflammation, repair, and remodeling together with stromal cells, progenitor cells, pro-inflammatory (M1 phenotype) macrophages, and anti-inflammatory (M2 phenotype) macrophages (Zou et al, 2021;Arostegui et al, 2022).…”
Section: Open Accessmentioning
confidence: 99%
“…In bone homeostasis, the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) is an important issue in the repair of bone injuries, including fracture healing and osteointegration at the prosthesis interface after joint replacement ( Wang et al, 2021 ). Once bone injuries occur, multiple signals trigger BMSCs in bone marrow or surrounding tissues to migrate to the injured regions and play a paracrine role ( Chen et al, 2021 ; Du et al, 2021 ; Sheng et al, 2022 ). In addition, BMSCs also have a hand in the healing stages of inflammation, repair, and remodeling together with stromal cells, progenitor cells, pro-inflammatory (M1 phenotype) macrophages, and anti-inflammatory (M2 phenotype) macrophages ( Zou et al, 2021 ; Arostegui et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%